1999
DOI: 10.1177/019262339902700302
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity/Oncogenicity Evaluation of 60 Hz (Power Frequency) Magnetic Fields in B6C3F1 Mice

Abstract: A 2-yr whole-body exposure study was conducted to evaluate the chronic toxicity and possible oncogenicity of 60 Hz (power frequency) magnetic fields in mice. Groups of 100 male and 100 female B6C3F 1 mice were exposed to pure, linearly polarized, transient-free 60 Hz magnetic fields at flux densities of 0 Gauss (G) (sham control), 20 milligauss (mG), 2 G, and 10 G; an additional group of 100 male and 100 female B6C3F 1 mice received intermittent (1 hr on/1 hr off) exposure to 10 G fields. A small but statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
0
26
1
1
Order By: Relevance
“…On this basis, the thyroid gland C-cell appears to be a relatively insensitive site for tumor induction. This factor, when considered together with (a) the lack of dose-response relationship for magnetic fields and C-cell tumors in male rats in the present study; (b) the lack of an increase in the incidence of preneoplastic lesions in C-cells in male rats in the present study; (c) the lack of a relationship between C-cell tumors and magnetic field exposure in female rats in the present study; (d) the lack of a relationship between C-cell tumors and magnetic field exposure in other chronic studies of power frequency magnetic field exposure in F344 rats (30,56) and B6C3F, mice (32) (companion paper to this manuscript); and (e) the lack of a correlate from epidemiological studies of magnetic fields and cancer, it appears unlikely that the observed relationship between magnetic fields and C-cell tumors in male rats is causal in nature.…”
Section: Discussioncontrasting
confidence: 52%
“…On this basis, the thyroid gland C-cell appears to be a relatively insensitive site for tumor induction. This factor, when considered together with (a) the lack of dose-response relationship for magnetic fields and C-cell tumors in male rats in the present study; (b) the lack of an increase in the incidence of preneoplastic lesions in C-cells in male rats in the present study; (c) the lack of a relationship between C-cell tumors and magnetic field exposure in female rats in the present study; (d) the lack of a relationship between C-cell tumors and magnetic field exposure in other chronic studies of power frequency magnetic field exposure in F344 rats (30,56) and B6C3F, mice (32) (companion paper to this manuscript); and (e) the lack of a correlate from epidemiological studies of magnetic fields and cancer, it appears unlikely that the observed relationship between magnetic fields and C-cell tumors in male rats is causal in nature.…”
Section: Discussioncontrasting
confidence: 52%
“…The 29 reports available for review since our previous publication (1) are listed in Table 1. These include 7 reports from 5 independent research groups describing results of singleor multigeneration chronic exposure studies, and 22 reports presenting results from 12 independent research groups conducting a variety of bioassays focused primarily on post-initiation stages of carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The three studies reported as in progress have now been completed (11)(12)(13)(14)(15). Studies that were complete at the time of our earlier review but that could not be evaluated because they were available only in preliminary or abstract form have now appeared in more complete form (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…En expérimentation animale, les études d'initiation (Mandeville et al, 1997 ;Yasui et al, 1997 ;McCormick et al, 1998McCormick et al, , 1999 et de promotion tumorale (Bernard et al, 2008 ;SCENIHR, 2009SCENIHR, , 2013, qui n'ont pas montré d'effet du champ magnétique, s'intègrent dans cette analyse.…”
Section: La Question Des Leucémies De L'enfantunclassified